PENGEMBANGAN FORMULIR DIGITAL RAPID CONVENIENCE ASSESSMENT IMUNISASI DASAR DAN LANJUTAN BERBASIS EPICOLLECT5 DATA COLLECTION DI PROVINSI BALI - Damadita, Putu Dwiki; Widarsa, I Ketut Tangking (ARCHIVE OF COMMUNITY HEALTH, 2021)
ABSTRACT Rapid Convenience Assessment (RCA) of immunization is an immunization coverage survey that is carried out as an assessment of the immunization program’s implementation. The process of data recording in RCA of immunization program had several problems, such as repeated data entry from the questionnaire into the computer, missing data, and problematic data. Epicollect5 Data Collection application can be used as a solution to solve these problems. This study aims to develop a digital form for RCA of immunization based on using Epicollect5 Data Collection.  This study used a participatory action research approach with the System Development Life Cycle (SDLC) development model, involving 11 immunization officers as the research’s subjects from the Health Office of Bali Province, Health Office of Denpasar City, Tabanan, Badung, and Gianyar Regency. The study was conducted from March to May 2020. The development of digital forms was carried out through three stages, namely identification of RCA information needs, development of digital form prototypes, and field tests. The digital form was created in the Epicollect5 Data Collection application and consists of 5 main parts, namely the form identity, location of the RCA immunization, respondent identity, basic immunization, and advanced immunization. The output data that can be generated from the epicollect website are tables of data, mapping, and simple analysis. The results of the field test conducted by 11 immunization officers indicate that the immunization officers support the use of digital forms in terms of performance expectancy, effort expectancy, and behavioral intention. It is hoped that the digital form can be used in the RCA immunization program carried out by the Health Office of Bali Province in the future. Keywords : Digital form development, RCA of immunization, Epicollect5 Data Collection